High-ductility geopolymer recycled concrete and preparation method thereof
By adding PVA fiber to the ground concentration and using raw materials such as slag powder, flour ash, and recycled sand to prepare high -delayed vertical regeneration concrete, solve the problem of insufficient tensile resistance and delay, and realize the materials. The intensity and latency are improved, while reducing production costs and environmental pollution.
Patent Information
- Application Number
- CN202411510766.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
Smart Images

Figure BDA0005105393650000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete, and in particular to a high-ductility geopolymer recycled concrete and a preparation method thereof. Background Art
[0002] Cement is a powdery, hydraulic, inorganic cementitious material. After adding water and stirring, it becomes a slurry, which can harden in the air or in water, and can firmly bond materials such as sand and stone together. Concrete made of crushed stone is not only strong after hardening, but also resistant to erosion by fresh water or salt water. For a long time, cement has been an important cementitious material and is widely used in civil engineering, water conservancy, national defense and other projects.
[0003] In 2022, the national cement production will be about 2.13 billion tons, accounting for more than 50% of the global total. At present, carbon emissions from cement production account for about 14% of the country's total carbon emissions, which is a key link in the carbon neutrality process in the construction field; my country's cumulative stockpile of bulk solid waste is about 60 billion tons, of which waste concrete accounts for about 40%, which is also a key area for comprehensive resource utilization.
[0004] Geopolymer concrete is a new type of environmentally friendly building material with the characteristics of high strength, corrosion resistance, and easy construction. It is usually used in underground facilities, water conservancy projects, chemical equipment and other fields. It is favored for its good chemical resistance and wear resistance. Compared with traditional concrete, geopolymer concrete is not easily corroded or cracked, and the formula can be adjusted as needed to meet specific engineering requirements. Therefore, it has certain application prospects in specific projects. However, geopolymer concrete is a highly brittle material like ordinary cement, with poor tensile properties and ductility, which restricts the application of geopolymer concrete.
[0005] The brittleness of geopolymer concrete is mainly due to the lack of buffering effect between cementitious materials and aggregates in traditional concrete when the material is subjected to loads. It is necessary to conduct experiments by adding raw materials to supplement this buffering effect. In addition, adding short-cut fibers with high elongation to the concrete matrix can further improve the toughness of geopolymer concrete. The use of industrial by-products, recycled aggregates and alkali activators to produce geopolymer recycled concrete can greatly alleviate the environmental and resource crises related to the concrete industry, and is also one of the effective ways to reduce carbon emissions at the source in the building materials industry.
[0006] It is of great significance to use geopolymers and recycled fine aggregate to prepare ultra-high ductility concrete, realize large-scale utilization of solid waste, and improve the green and low-carbon nature of building materials. Summary of the invention
[0007] In view of this, the present invention provides a high-ductility geopolymer recycled concrete, which uses industrial solid wastes such as slag powder and fly ash, and recycled sand as main raw materials, which can not only reduce energy consumption and reduce environmental pollution, but also reduce the preparation cost of ultra-high ductility geopolymer-based recycled concrete.
[0008] The present invention provides the following technical solutions:
[0009] A high-ductility geopolymer recycled concrete comprises the following raw materials in parts by weight: 200-250 parts of slag powder, 900-950 parts of fly ash, 350-420 parts of recycled sand, 15-30 parts of PVA fiber, 400-450 parts of alkali activator, 5-10 parts of water reducer and 80-90 parts of water.
[0010] Preferably, the specific surface area of the slag powder is 400 to 500 m 2 / kg, density is 2500~3000kg / m 3 .
[0011] Preferably, the specific surface area of the fly ash is 500-600m 2 / kg, density is 2500~3000kg / m 3 .
[0012] Preferably, the apparent density of the regenerated sand is 2600 kg / m 3 , particle size range is 7-14mm.
[0013] Preferably, the Young's modulus of the PVA fiber is 40.0 GPa, the elongation is 6.0%, and the nominal strength is 1600 MPa.
[0014] Preferably, the alkaline activator is prepared by mixing sodium silicate, sodium hydroxide and water; the modulus of the alkaline activator is 1.4 to 1.6.
[0015] Preferably, the water reducer is a polycarboxylate water reducer.
[0016] The method for preparing the high-ductility geopolymer recycled concrete comprises the following steps:
[0017] (1) Ingredients: Slag powder, fly ash, regenerated sand, PVA fiber, water reducer and water are weighed in proportion, and an alkali activator is prepared, and then part of the water and the water reducer are mixed evenly to obtain a water reducer solution;
[0018] (2) stirring and mixing: the fly ash, slag powder and regenerated sand are stirred at a low speed for 2 to 4 minutes until they are uniform, and then the alkali activator is slowly poured thereinto, and after stirring at a low speed for 1 to 2 minutes, the water reducing agent solution is added, and stirred at a high speed for 2 to 3 minutes, and finally the PVA fiber is added, and stirred at a high speed for 4 to 6 minutes to obtain a mixed slurry;
[0019] (3) Molding: pouring the mixed slurry into a mold, molding for 24 hours, and then removing the mold to obtain a concrete body;
[0020] (4) De-moulding and curing: the concrete body is subjected to high temperature curing and constant temperature and humidity curing in sequence to obtain the high-ductility geopolymer recycled concrete.
[0021] Preferably, the stirring rate of the low-speed stirring in step (2) is 140±10 r / min; and the stirring rate of the high-speed stirring is 250±10 r / min.
[0022] Preferably, the high temperature curing in step (4) is performed at 60-65°C for 20-24 hours; and the constant temperature and humidity curing is performed in a constant temperature and humidity curing room at a temperature of 20±2°C and a humidity of 95±2% for 28 days.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention toughens geopolymer concrete by adding PVA fibers, utilizes the interfacial bonding effect between the matrix and the polyethylene fibers, increases the tensile strain capacity of the material, and solves the problem of high brittleness of geopolymer concrete.
[0025] 2. The slag powder and fly ash used in the present invention are derived from industrial solid waste, and the regenerated sand is derived from construction waste and abandoned concrete. Using the above waste as the material source for concrete can not only reduce energy consumption and reduce pollution to the environment, but also reduce the preparation cost of ultra-high ductility geopolymer-based recycled concrete.
[0026] 3. The addition of an appropriate amount of fly ash in the present invention will make the concrete have higher strength and toughness. The activation reaction of fly ash and alkali activator is stable. The silicon aluminum oxide in the fly ash reacts with the alkali activator to form a gel structure of calcium silicate hydrate (CSH), which helps to enhance the strength and durability of the concrete. The fly ash has a small particle size and can fill the tiny pores in the concrete, reducing the shrinkage of the concrete and the generation of cracks; at the same time, the high silica content and spherical particle structure in the fly ash can effectively improve the permeability and cracking tendency of the concrete, prevent the infiltration of external corrosive substances, and effectively reduce the risk of corrosion, cracking and aging of the concrete. The appropriate amount of fly ash added can also reduce the friction bonding strength between the matrix and the fiber, which is beneficial to the slippage of the fiber in the matrix.
[0027] 4. The present invention performs fiber toughening treatment on geopolymer concrete and forms a buffer layer with recycled sand to alleviate the friction and impact between the sand and cementitious materials, improve the brittleness of geopolymer concrete, and then prepare a low-carbon economy, excellent mechanical properties, high-ductility slag-fly ash-based geopolymer recycled concrete with strain hardening characteristics, thereby realizing the recycling of industrial solid waste and waste concrete. DETAILED DESCRIPTION
[0028] A high-ductility geopolymer recycled concrete comprises the following raw materials in parts by weight: 200-250 parts of slag powder, 900-950 parts of fly ash, 350-420 parts of recycled sand, 15-30 parts of PVA fiber, 400-450 parts of alkali activator, 5-10 parts of water reducer and 80-90 parts of water.
[0029] The specific surface area of the slag powder is 400-500m 2 / kg, density is 2500~3000kg / m 3 .
[0030] The specific surface area of the fly ash is 500-600m 2 / kg, density is 2500~3000kg / m 3 .
[0031] The apparent density of the regenerated sand is 2600 kg / m 3 , particle size range is 7-14mm.
[0032] The PVA fiber has a Young's modulus of 40.0 GPa, an elongation of 6.0%, and a nominal strength of 1600 MPa.
[0033] The alkaline activator is prepared by mixing sodium silicate, sodium hydroxide and water; the modulus of the alkaline activator is 1.4-1.6.
[0034] The water reducer is a polycarboxylate water reducer.
[0035] In a specific embodiment of the present invention, the slag powder is S95 grade granulated blast furnace slag with a specific surface area of 459m 2 / kg, density 2930kg / m 3 The fly ash is Class F primary fly ash with a specific surface area of 513m 2 / kg, density 2620kg / m 3 The particle size of the slag powder is 10-100um; the particle size of the fly ash is 10-80um.
[0036] In a specific embodiment of the present invention, the regenerated sand is derived from construction waste and waste concrete; the apparent density of the regenerated sand is 2600 kg / m 3, particle size range is 70-140mm.
[0037] In a specific embodiment of the present invention, the PVA fiber has a Young's modulus of 40.0 GPa, an elongation of 6.0%, and a nominal strength of 1600 MPa;
[0038] In a specific embodiment of the present invention, the preparation method of the alkaline activator is: Na2SiO3 (modulus is 2.8) and NaOH (solid flaky particles with a purity of 99.0%) are added to water to form a solution with a mass fraction of 40%, and the solution is allowed to stand for 12 hours. When used, the Na2SiO3 solution and the NaOH solution are mixed in a volume ratio of 2.8:1 to obtain an alkaline activator solution with a modulus of 1.6.
[0039] In a specific embodiment of the present invention, the water reducer is C1029 polycarboxylate water reducer, which is a product commonly purchased on the market.
[0040] The method for preparing the high ductility geopolymer recycled concrete comprises the following steps:
[0041] (1) Ingredients: Slag powder, fly ash, regenerated sand, PVA fiber, water reducer and water are weighed in proportion, and an alkali activator is prepared. A portion of water is taken and mixed with the water reducer in a mass ratio of 10:1 to obtain a water reducer solution;
[0042] (2) Stirring and mixing: Fly ash, slag powder and regenerated sand are stirred at a low speed (stirring rate is 140±10r / min) for 2 to 4 minutes until they are uniform, and then the alkali activator is slowly poured thereinto, and stirred at a low speed (stirring rate is 140±10r / min) for 1 to 2 minutes, and then the water reducing agent solution is added, and stirred at a high speed (stirring rate is 250±10r / min) for 2 to 3 minutes, and finally PVA fiber is added, and stirred at a high speed (stirring rate is 250±10r / min) for 4 to 6 minutes to obtain a mixed slurry;
[0043] (3) Molding: pouring the mixed slurry into a mold, molding for 24 hours, and then removing the mold to obtain a concrete body;
[0044] (4) De-moulding and curing: the concrete body is placed in a 60°C oven for high-temperature curing. After 24 hours, the concrete body is taken out and placed in a constant temperature and humidity curing room at a temperature of (20±2)°C and a humidity of (95±2)% for curing for 28 days to obtain the high-ductility geopolymer recycled concrete.
[0045] In a specific embodiment of the present invention, the PVA fibers are slowly and evenly sprinkled along the rotation direction of the mixer.
[0046] In a specific embodiment of the present invention, the specific method of molding is: first, pour the mixed slurry into the mold, vibrate it on a high-speed vibration table for two minutes, during which time use a vibrating rod to vibrate along the edge of the mold to eliminate bubbles, smooth the surface, and then cover the surface of the sample with a plastic film to prevent water loss.
[0047] The present invention is further described below with reference to the examples. In the specific examples of the present invention, the parts are all "parts by mass" and, unless otherwise specified, conventional raw materials and methods in the art are used.
[0048] Example 1
[0049] A high-ductility geopolymer recycled concrete, comprising the following raw materials in parts by weight:
[0050] 230 parts of slag powder, 923 parts of fly ash, 403 parts of regenerated sand, 26 parts of PVA fiber, 432 parts of alkali activator, 9 parts of water reducer, and 87 parts of water.
[0051] The method for preparing the high ductility geopolymer recycled concrete comprises the following steps:
[0052] (1) Ingredients: Slag powder, fly ash, regenerated sand, PVA fiber, water reducer and water are weighed in proportion, and an alkali activator is prepared, and then part of the water and the water reducer are mixed evenly to obtain a water reducer solution;
[0053] (2) Mixing: Evenly mix the fly ash, slag powder and regenerated sand and put them into a planetary mortar mixer and stir at a low speed (stirring rate is 140±10r / min) for 2 minutes until they are uniform. Then slowly pour the alkali activator into them and stir at a low speed (stirring rate is 140±10r / min) for 1 minute. Then add the water reducing agent solution and stir at a high speed (stirring rate is 250±10r / min) for 2 minutes. Finally, slowly and evenly sprinkle the PVA fiber along the rotation direction of the mixer and stir at a high speed (stirring rate is 250±10r / min) for 6 minutes to obtain a mixed slurry.
[0054] (3) Molding: First, pour the mixed slurry into the mold and vibrate it on a high-speed vibration table for two minutes. During this time, use a vibrating rod to vibrate along the edge of the mold to eliminate bubbles and smooth the surface. Then, cover the surface of the sample with a plastic film to prevent water loss. After molding for 24 hours, remove the mold to obtain the concrete body.
[0055] (4) De-moulding and curing: the concrete body is placed in a 60°C oven for high-temperature curing. After 24 hours, the concrete body is taken out and placed in a constant temperature and humidity curing room at a temperature of (20±2)°C and a humidity of (95±2)% for curing for 28 days to obtain the high-ductility geopolymer recycled concrete.
[0056] Example 2
[0057] A high-ductility geopolymer recycled concrete, comprising the following raw materials in parts by weight:
[0058] 230 parts of slag powder, 923 parts of fly ash, 403 parts of regenerated sand, 23 parts of PVA fiber, 432 parts of alkali activator, 8 parts of water reducer, and 87 parts of water.
[0059] The preparation method of the high ductility geopolymer recycled concrete is the same as that in Example 1.
[0060] Example 3
[0061] A high-ductility geopolymer recycled concrete, comprising the following raw materials in parts by weight:
[0062] 230 parts of slag powder, 923 parts of fly ash, 403 parts of regenerated sand, 19 parts of PVA fiber, 432 parts of alkali activator, 9 parts of water reducer, and 87 parts of water.
[0063] The preparation method of the high ductility geopolymer recycled concrete is the same as that in Example 1.
[0064] Example 4
[0065] A high-ductility geopolymer recycled concrete, comprising the following raw materials in parts by weight:
[0066] 115 parts of slag powder, 1035 parts of fly ash, 403 parts of regenerated sand, 26 parts of PVA fiber, 432 parts of alkali activator, 9 parts of water reducer, and 87 parts of water.
[0067] The preparation method of the high ductility geopolymer recycled concrete is the same as that in Example 1.
[0068] Example 5
[0069] A high-ductility geopolymer recycled concrete, comprising the following raw materials in parts by weight:
[0070] 348 parts of slag powder, 810 parts of fly ash, 403 parts of regenerated sand, 26 parts of PVA fiber, 432 parts of alkali activator, 7 parts of water reducer, and 87 parts of water.
[0071] The preparation method of the high ductility geopolymer recycled concrete is the same as that in Example 1.
[0072] Comparative Example 1
[0073] A high-ductility geopolymer recycled concrete, comprising the following raw materials in parts by weight:
[0074] 815 parts of fly ash, 403 parts of regenerated sand, 26 parts of PVA fiber, 432 parts of alkali activator, 9 parts of water reducer, and 87 parts of water.
[0075] The preparation method of the high-ductility geopolymer recycled concrete is as shown in Example 1.
[0076] Comparative Example 2
[0077] A high-ductility geopolymer recycled concrete, comprising the following raw materials in parts by weight:
[0078] 230 parts of slag powder, 923 parts of fly ash, 403 parts of regenerated sand, 432 parts of alkali activator, 9 parts of water reducer, and 87 parts of water.
[0079] The preparation method of the high-ductility geopolymer recycled concrete is as shown in Example 1.
[0080] After curing for 28 days, the mechanical properties of the high ductility geopolymer recycled concrete in Examples 1 to 5 and Examples 1 to 2 were tested. The results are shown in Table 1.
[0081] Table 1
[0082]
[0083] Table 1 d is the density, f cu is the compressive strength of concrete cube, f cu,3d , f cu,7d , f cu,28d Respectively represent the compressive strength of the cube after curing for 3 days, 7 days, and 28 days, f t,28d Indicates the tensile strength of concrete at 28 days.
[0084] By comparing Examples 1, 2, 3 and Comparative Example 2, as the PVA fiber content increased from 1.5% to 2% and then decreased to 0, the compressive strength of the concrete increased from 74.25MPa to 76.53MPa and then decreased to 75.12, and the increase and decrease were not obvious. It can be seen that the change in fiber content has no significant effect on the compressive strength of EGC, but in the absence of fibers, the tensile strength of the concrete decreases significantly. This is because the fiber plays a bridging role in the concrete, which can inhibit the development of the crack width, thereby increasing the peak strain of the concrete, achieving strain hardening, and increasing the tensile strength.
[0085] The effect of slag content on the compressive strength of the concrete is obvious. The compressive strengths of EGC with 0%, 20% and 30% slag content are 44.65MPa, 45.76MPa and 76.53MPa respectively. This is mainly because slag has a higher degree of reaction, forms more gel phase and a denser microstructure. Compared with fly ash, slag generally has higher reactivity and better bonding properties, mainly due to its high CaO content, which improves the early strength of geopolymer composites.
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high ductility geopolymer recycled concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 200-250 parts of slag powder, 900-950 parts of fly ash, 350-420 parts of regenerated sand, 15-30 parts of PVA fiber, 400-450 parts of alkali activator, 5-10 parts of water reducer and 80-90 parts of water.
2. The high ductility geopolymer recycled concrete according to claim 1, characterized in that: The specific surface area of the slag powder is 400-500m 2 / kg, density is 2500~3000kg / m 3 .
3. The high ductility geopolymer recycled concrete according to claim 1, characterized in that: The specific surface area of the fly ash is 500-600m 2 / kg, density is 2500~3000kg / m 3 .
4. The high ductility geopolymer recycled concrete according to claim 1, characterized in that: The apparent density of the regenerated sand is 2600 kg / m 3 , particle size range is 7-14mm.
5. The high ductility geopolymer recycled concrete according to claim 1, characterized in that: The Young's modulus of the PVA fiber is 40.0 GPa, the elongation is 6.0%, and the nominal strength is 1600 MPa.
6. The high ductility geopolymer recycled concrete according to claim 1, characterized in that: The alkaline activator is prepared by mixing sodium silicate, sodium hydroxide and water; the modulus of the alkaline activator is 1.4-1.
6.
7. The high ductility geopolymer recycled concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.
8. The method for preparing high ductility geopolymer recycled concrete according to claim 1, characterized in that: The following steps are involved: (1) Ingredients: Slag powder, fly ash, regenerated sand, PVA fiber, water reducer and water are weighed in proportion, and an alkali activator is prepared, and then part of the water and the water reducer are mixed evenly to obtain a water reducer solution; (2) stirring and mixing: the fly ash, slag powder and regenerated sand are stirred at a low speed for 2 to 4 minutes until they are uniform, and then the alkali activator is slowly poured thereinto, and after stirring at a low speed for 1 to 2 minutes, the water reducing agent solution is added, and stirred at a high speed for 2 to 3 minutes, and finally the PVA fiber is added, and stirred at a high speed for 4 to 6 minutes to obtain a mixed slurry; (3) Molding: pouring the mixed slurry into a mold, molding for 24 hours, and then removing the mold to obtain a concrete body; (4) De-moulding and curing: the concrete body is subjected to high temperature curing and constant temperature and humidity curing in sequence to obtain the high-ductility geopolymer recycled concrete.
9. The method for preparing high ductility geopolymer recycled concrete according to claim 8, characterized in that: The stirring rate of the low-speed stirring in step (2) is 140±10 r / min; the stirring rate of the high-speed stirring is 250±10 r / min.
10. The method for preparing high ductility geopolymer recycled concrete according to claim 8, characterized in that: The high temperature curing in step (4) is curing at 60-65° C. for 20-24 hours; the constant temperature and humidity curing is curing in a constant temperature and humidity curing room at a temperature of 20±2° C. and a humidity of 95±2% for 28 days.